Efektifitas Garis Bilangan Untuk Meningkatkan Operasi Pengurangan Bagi Anak Tunarungu Kelas D.I.B di SDLB Manggis Ganting Bukittinggi (single Subject Research) - Dewi - Handayani (Universitas Negeri Padang, 2014)
Abstract: The data demonstrate the stability of the fifteenth meeting to meeting to tujgh twelve with the highest score of 100 % , with the results of the students were able to do all the questions . Later in the baseline condition with no treatment is given , the data shows the stability of the meeting to meeting to eighteen to twenty- two with the highest score of 100 % , with the results of the students were able to do all the questions . It can be concluded that the use of the media can increase the number line numbers subtraction operation ability of deaf children 1-10 DIB class SDLB Manggis Ganting Bukittinggi . It is suggested to the principal and teachers to make the results of this study as a reference for the development of mathematics learning in school .